Comparing the Effect of Room Air versus Commercially Available Oxygen for the Resuscitation of Asphyxiated Neonates in Kabul City: A Randomised Clinical Trial - Mansoor Aslamzai; Mohammad Farouq Hamidi; Zemary Hassin (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Perinatal asphyxia is one of the leading causes of neonatal death in Afghanistan. Recent recommendation has accepted room air as preferred therapy in the resuscitation of asphyxiated term neonates. Since the quality of air is poor in Kabul city so a study was needed to assess its efficacy in the resuscitation of neonates. Aim: To evaluate the effectiveness of room air versus commercially available oxygen for the resuscitation of asphyxiated term and preterm neonates. Materials and Methods: This study was a randomised clinical trial conducted at Neonatology ward of Malalai Hospital in Kabul city, Afghanistan. Total 300 neonates of 30-41 weeks gestation diagnosed as severe perinatal asphyxia were randomly resuscitated with either room air or commercially available oxygen. The clinical parameters were the Apgar score, oxygen saturation and neonatal mortality percentage. Statically analysis was performed by SPSS 20. Results: One hundred and fifty neonates in the room air group and 150 neonates in commercially available oxygen group were investigated. The term neonate percentage was 76% and 75.3% in the room air and oxygen group respectively. Term neonates resuscitated with room air had obtained higher mean oxygen saturation (83.4±14.9, p=0.001) than oxygen (77.1±13.1, p=0.001) at 5 minute of birth. Median Apgar score was the same in both groups (5, p=0.001). The difference of mortality during hospital stay in both groups was not statistically significant (5.26% vs 7%, p=0.59). Mean oxygen saturation in preterm newborn babies were 80.58±15.62 and 78.41±11.91 with p=0.22, respectively in both groups. Median Apgar score in room air was 6 and in oxygen group was 5 with p=0.33. Preterm infant also showed non-significant difference of mortality during hospital stay in both groups (11.1% vs 18.9%, p=0.5). Conclusion: Despite poor air quality in Kabul city, room air was significantly more effective than commercially available oxygen to increase oxygen saturation and as effective as commercially available oxygen to elevate Apgar scores in the resuscitation of asphyxiated term neonates. The difference in the mortality was not statistically significant in both the groups. The efficacy of room air did not appear statistically significant for the resuscitation of preterm neonates.